2018
DOI: 10.21037/tau.2018.04.19
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intra-operative cell salvage during open radical prostatectomy

Abstract: BackgroundTo examine the effect of intra-operative cell salvage (ICS) in open radical prostatectomy.MethodsIn this retrospective cohort study, all patients undergoing open radical prostatectomy for malignancy at our institution between 10/04/2013 and 10/04/2017 were enrolled. Patients were grouped and compared based on whether they received ICS. Primary outcomes were allogeneic transfusion rates, and disease recurrence. Secondary outcomes were complications and transfusion-related cost.ResultsFifty-nine men we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…Indeed, existing meta-analysis of blood conservation strategies in oncological surgery have revealed higher rates of disease recurrence with allogeneic transfusion (8,9), but not ICS (13,14). Amongst all twelve comparative studies to date of ICS in radical prostatectomy, with study follow up ranging 0-64 months (median 36 months), groups receiving ICS have experienced similar or decreased rates of biochemical recurrence compared with controls (10,14).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, existing meta-analysis of blood conservation strategies in oncological surgery have revealed higher rates of disease recurrence with allogeneic transfusion (8,9), but not ICS (13,14). Amongst all twelve comparative studies to date of ICS in radical prostatectomy, with study follow up ranging 0-64 months (median 36 months), groups receiving ICS have experienced similar or decreased rates of biochemical recurrence compared with controls (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with similar works. While three prior studies of ICS in prostatectomy have reported significantly reduced ABT rates (35)(36)(37), most have not (10,(37)(38)(39)(40)(41)(42)(43)(44)(45). In our patients, we believe this is related to the high median pre-operative haemoglobin (152-154 g/L), low rates of transfusion in both groups (2-5%) and small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations